Enhancing wear resistance of CoNiCrMo medium entropy alloy through cold working and aging: Tradeoffs with corrosion performance - Elham Rahimi; Mohammad Rezayat; Soheil Mahdavi (Journal of Materials Research and Technology)
This study investigates the wear behavior and corrosion resistance of MP35 N alloy under various conditions, including annealed, cold-worked, and aged states. The microstructure was characterized using optical microscopy, X-ray diffraction, and transmission electron microscopy. Results indicated that cold rolling induced a dislocation structure and deformation features such as mechanical twins, stacking faults, and slip bands. The presence of non-homogeneous strain and planar defects in the cold-rolled samples led to broader diffraction peaks compared to the annealed samples. The microstructure of the cold-rolled and artificially aged samples exhibited deformation features, dislocation structures, and ultra-fine precipitates. High-angle annular dark field imaging and energy-dispersive X-ray spectroscopy revealed that these precipitates were Ti-rich particles, which, along with molybdenum segregation in stacking faults, contributed to the highest hardness observed. X-ray diffraction analysis confirmed the segregation and depletion of alloying elements from the lattice during aging. Wear and corrosion tests demonstrated that while cold working and aging enhanced the wear performance of the annealed CoNiCrMo alloy, they adversely affected its corrosion resistance. Specifically, the volume loss for cold-worked and aged samples was approximately 2.7 and 2.1 times smaller than that of the annealed specimen, respectively. However, the annealed alloy exhibited a lower corrosion current density (icorr) of 70 nA cm−2 compared to the cold-worked and aged samples, which had icorr values of 130 and 200 nA cm−2, respectively.